Eu vou entrar no mundo : experiências de trabalhadores migrantes na região de Ribeirão Preto - 1980-2007 - Nasser, Sérgio Daniel (2008)
In this research have been analyzed the experiences of migrants workers that arrived at the region of Ribeirão Preto in decades 1980, 1990 and 2000. We seek to understand the actions of these citizens in the transformation of the region, as well as the conflicts that they experienced with other local groups for the conquest of the space and the right of belonging in the place. For the analysis of the interviews realized with the workers we could observe the forms of survival created by these citizens in the region of Ribeirão Preto, based in complicity relations that make possible the arrival, the permanence and the survival in the place. We still observed the tensions around the question of the migration for the region of Ribeirão Preto from years 1980, when local sectors have started to debate the presence of the migrant in the place, constructing interpretations that, many times, criminalized the presence of these citizens and charged the public intervention by means of the creation of the centers of selections.